Characterization of two genes required for the position-effect control of yeast mating-type genes. - Shore, D (1984)
The mating type of haploid yeast (a or alpha) is determined by information present at the MAT locus. Identical copies of a and alpha information are present at distal loci (HMR and HML), but transcription of these copies is repressed by the action, in trans, of four unlinked genes called SIR (silent information regulator). Repression by SIR also requires, in cis, DNA sequences called E which are found to the left of HML and HMR (but not MAT) and are greater than 1 kb from the mating-type gene promoters. SIR control can act on other promoters when they are brought near the E sequence, and thus the SIR gene products act in some general manner to repress transcription. We have determined the DNA sequence of two fragments which complement mutations in the SIR2 and SIR3 genes and show that these contain the structural genes by mapping the cloned sequences onto the yeast chromosome. The SIR2 and SIR3 coding sequences were identified by constructing gene disruptions and using these mutations to replace the normal chromosomal copies. Such null mutants of both SIR2 and SIR3 are defective in the position-effect control of the silent loci but have no other detectable phenotype. We have mapped the 5' and 3' ends of the SIR2 and SIR3 mRNAs and show that their level is unaffected by mutations in any of the four known SIR complementation groups.